MG-135 P300 regulates glucose homeostasis by maintaining islet mass. (4th December 2015) - Wong, Chi Kin; Lynn, Francis; Brindle, Paul; Gibson, William
Abstract : We recently identified a patient with Rubinstein-Taybi syndrome (RTS) who also had early-onset diabetes at the age of 23 years despite a thin body mass index of 23 kg per sq.metre. She has retained endogenous insulin production and is controlled on oral hypoglycemics. Such a phenotype has not been associated with RTS previously. RTS is caused by autosomal dominant mutations in CREBBP or EP300; she had a microdeletion affecting one EP300 allele. p300 is an important transcriptional coactivator with histone acetyltransferase activity. Other studies have suggested that p300 coactivates NeuroD1, HNF4a and PDX1, which are transcription factors important for beta cell function and identity. Based on these lines of evidence, we hypothesised that p300 is required to maintain beta cell function, and that deletion of one allele of the gene may cause the diabetes in our patient. To test this hypothesis, we have generated mice missing p300 in Ngn3 + pancreatic islets by the Cre-loxP system. Mice lacking p300 in their pancreatic islets develop glucose intolerance at the age of eight weeks, which is caused by hypoinsulinemia. These phenotypes recapitulated a key portion of our patient's phenotype. Immunostaining confirmed reduced total islet mass in the pancreata of p300 IsletKO mice, involving the loss of both beta cells and alpha cells. At the cellular level, p300-null islets display normal insulin synthesis and glucose-stimulated insulin secretion. We carried out RNA-seq and qPCR to identify transcriptome-wide changes in p300-null islets. We found that several genes previously associated with islet proliferation are differentially expressed. Our experiments suggest that p300 acts as a critical regulator of islet mass and that its expression in islets is required for maintaining glucose homeostasis. The project is supported by Canucks for Kids diabetes catalyst grant and NSERC discovery grant (RGPIN 402576–11).